FORMA Y MOVIMIENTO EN LOS ESTUDIOS LITERARIOS - Alfaro Vargas, Roy (Universidad de Costa Rica, 2013)
This article analyzes the different roads of development of the literary studies, in accordance with the logical pattern of which leave, that is to say, the application of the dialectical logic bears for the literary studies an emphasis in the content and its movement, while, with the formal logic, these they emphasize the form, that derives in a preponderance of the descriptive thing.